VD_FINDINFO HC / 2014 / 308 vom 27. März 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, BAIL À LOYER, LOCAL PROFESSIONNEL, SOUS-LOCATION, PAIEMENT DE L'ARRIÉRÉ | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 271 al. 1 CO, 271 CO